2016
DOI: 10.1186/s12903-016-0291-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of occlusal caries detection using the ICDAS criteria on extracted teeth or their photographs

Abstract: BackgroundUsing photographs of occlusal surfaces instead of extracted teeth for the detection of caries can be useful in multicenter studies or education. Using a panel of observers, ICDAS scores on teeth or photographs were evaluated against the histological gold standard. The hypothesis was that both outcomes were equivalent.MethodsFour examiners with different experience in ICDAS scored photographs of occlusal surfaces of 100 extracted teeth on a monitor using ICDAS criteria. Two of the examiners had previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…The photographs of carious lesions were used for ICDAS‐II‐SSCm scoring. The effect of photograph on observer's performance had already been examined and showed no significant difference in sound surfaces or those with ICDAS‐II scores 1‐4 . After saving photographs of ICDAS‐II‐SSCm scoring, the first and/or third author (SV& SM) proceeded to other centre for PS‐OCT procedure to reduce overall time consumption to avoid any effect of storing medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The photographs of carious lesions were used for ICDAS‐II‐SSCm scoring. The effect of photograph on observer's performance had already been examined and showed no significant difference in sound surfaces or those with ICDAS‐II scores 1‐4 . After saving photographs of ICDAS‐II‐SSCm scoring, the first and/or third author (SV& SM) proceeded to other centre for PS‐OCT procedure to reduce overall time consumption to avoid any effect of storing medium.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of photograph on observer's performance had already been examined and showed no significant difference in sound surfaces or those with ICDAS-II scores 1-4. 26 After saving photographs of ICDAS-II-SSCm scoring, the first and/or third author (SV& SM) proceeded to other centre for PS-OCT procedure to reduce overall time consumption to avoid any effect of storing medium. A bias of perception between the examiners was decreased in the study by using the same laptop with similar contrast and brightness for all the examiners amid scoring.…”
Section: F I G U R E 3 Sensitivity and Specificity Values For Icdas-ii-mentioning
confidence: 99%
“…This has been also found in other studies, as visual examination presents some difficulties in distinguishing between active caries and non-carious hard tissue defects or inactive lesions. 25,27 Moreover, we also attribute this result to the type of gold standard used in the present study, which evaluated the lesions on a three-dimensional basis and relied on quantitative cutoff mineral density values. Collectively, the low sensitivity values for threshold 2 and low specificity values for threshold 1 found in the present study may emphasize the effect of an alternative micro-CT gold standard.…”
Section: Discussionmentioning
confidence: 93%
“…One of the main limitations on the more widespread use of ICDAS as a caries scoring system is the difficulty in achieving inter-examiner agreement, since each examiner is expected to have a different interpretation of visual signs based on personal visual acuity, neural signal processing, experience, and education. 25 A previous study found that e-learning sessions on ICDAS along with training sessions performed with instructors on extracted teeth improved the ability of dental students to apply the ICDAS criteria for diagnostic purposes. 29 In this study, calibration with e-learning sessions on ICDAS was performed to check whether a less demanding learning curve could be expected from this scoring system involving relatively experienced dental professionals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation